2007
DOI: 10.1007/s11682-007-9006-z
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Study of Frontal–Subcortical Skeletomotor Circuit and Dorsolateral Prefrontal Cortex Function Using a Paced Motor Activation Paradigm

Abstract: The frontal-subcortical skeletomotor circuit is thought to be a motor processing network. However, the exact function of the circuit is poorly characterized. This fMRI study utilized a motor activation paradigm for both hands to probe circuit engagement and connectivity. Activation of the circuit decreased over time for the right hand, which suggests circuit engagement can vary during task execution. Changes in activation of the right dorsolateral prefrontal cortex were highly correlated with changes in activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In particular, growing evidence suggests that nuclei connected by inhibitory fibers do in fact exhibit strong functional connectivity. For example, we have previously found that basal ganglia intrinsic structures receiving primarily inhibitory input activate during motor task execution [Marchand et al, 2007b]. Further, we have reported [Marchand et al, 2007d] failure to find evidence of deactivation among basal ganglia intrinsic structures that receive inhibitory input during motor behavior.…”
Section: Intrinsic Pathwaysmentioning
confidence: 89%
“…In particular, growing evidence suggests that nuclei connected by inhibitory fibers do in fact exhibit strong functional connectivity. For example, we have previously found that basal ganglia intrinsic structures receiving primarily inhibitory input activate during motor task execution [Marchand et al, 2007b]. Further, we have reported [Marchand et al, 2007d] failure to find evidence of deactivation among basal ganglia intrinsic structures that receive inhibitory input during motor behavior.…”
Section: Intrinsic Pathwaysmentioning
confidence: 89%
“…A human fMRI study revealed that neuronal activity of specific basal ganglia nuclei is affected by whether feedback is derived from visual or auditory inputs providing evidence of convergence of sensory input with motor output information (Prodoehl et al 2008). Another study demonstrated functional connectivity of the putamen with the DLPFC during motor task execution providing evidence of the integration of motor and cognitive information (Marchand et al 2007a). A rodent study (Kasanetz et al 2008) of the striatal up states discussed above revealed that the coordination between cortical areas and striatal regions obeys a mediolateral gradient and tracks slow wave trajectories across the neocortex.…”
Section: The Evidence For Integrationmentioning
confidence: 99%
“…As a result, we also discuss how person-environment interactions influence and direct the pattern of deficits or strengths individuals with acquired neurodevelopmental conditions present with over time. Specifically, we propose that many of the neuropsychological sequelae associated with the disorders discussed in this chapter, including executive dysfunction, mood disturbance, and psychotic symptoms, reflect a primary disruption in the unfolding development of frontal-subcortical circuitry (marchand et al, 2007;tekin & Cummings, 2002), leading to an altered trajectory of cognitive, behavioral, and emotion regulation across time. Available evidence from specific imaging studies is presented in table 12.1 to elucidate these relationships.…”
mentioning
confidence: 99%